Computed tomography-derived characterisation of pericoronary, epicardial and paracardial adipose tissue and its association with myocardial ischemia as assessed by computed and invasive fractional flow. (14th October 2021) - Goeller, M; Duncker, H; Moshage, M; Dey, D; Bittner, D; Ammon, F; Achenbach, S; Marwan, M
Abstract: Introduction: Increased pericoronary adipose tissue (PCAT) computed tomography (CT) attenuation derived from coronary CT angiography (CTA) around the right coronary artery (RCA) reflects coronary inflammation and relates to cardiac mortality. Purpose: We aimed to investigate the yet unclear association between CT-derived characterisation of different cardiac adipose tissue compartments and the presence of myocardial ischemia as assessed by fractional flow reserve (FFR). Methods: 133 stable individuals (64 years, 74% male) with coronary artery disease (CAD) underwent CTA including computed FFR (FFR-CT) measurement followed by invasive angiography with FFR (invasive FFR) assessment. The CT attenuation (HU) and volume (mm 3 ) of PCAT were quantified around the RCA (10 to 50 mm from RCA ostium), the proximal 40 mm of the left anterior descending artery (LAD) and the circumflex artery (LCX) with the help of semi-automated software. The per patient PCAT CT attenuation was calculated as followed: (PCAT CT attenuation of RCA+LAD+LCX)/3. Quantification of epicardial adipose tissue (EAT) and paracardial adipose tissue (PAT; all intrathoracic adipose tissue outside the pericardium) were performed in non-contrast cardiac CT data sets using a fully automated deep-learning based algorithm. Results: Median FFR-CT was 0.86 [0.79, 0.91] and median invasive FFR was 0.87 [0.81, 0.93]. Patients with presence of myocardial ischemia (n=26) defined by a FFR-CT threshold of ≤0.75 showed a significant higher PCAT CT attenuation of RCA (−75.1 HU vs. −81.1 HU, p=0.011) and per patient (−74.5 HU vs. −77.7 HU, p=0.045) than individuals without myocardial ischemia (n=107). In multivariable analysis adjusted for age, BMI, gender and traditional risk factors, both RCA and per patient PCAT CT attenuation were significant predictors of myocardial ischemia as assessed by FFRCT ≤0.75. Between individuals with myocardial ischemia compared to individuals without myocardial ischemia there was no significant difference neither in the volume and CT attenuation of EAT and PAT nor in the PCAT volume of RCA, LAD, LCX and per patient PCAT volume. Conclusions: Our observations suggest that PCAT CT attenuation instead of PCAT volume, EAT and PAT measures might be associated with the presence of myocardial ischemia as assessed by FFR. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): German Heart Foundation e.V.